Pengaruh Kompetensi Terhadap Kinerja Pegawai Di Badan Perpustakaan, Arsip dan Dokumentasi Kota Denpasar - Cahyaningrat, A.A Made Bintang; Erviantono, Tedi; Wismayanti, Kadek Wiwin Dwi (CITIZEN CHARTER, 2017)
ABSTRACT Competence of employees is very important in the organization. These competencies will create a superior employee performance and effective in carrying out the work. Technological change rapid will lead human resources to understand technological development, so the employee needed is competence of employee sufficient and able to use the technology. The problem underlying this study is the average employees only graduated of senior high school (SMA) graduated which is its haven’t achieve the minimal standard level of  archieve proffesion and not all employee can operate the information technology such as computers.The method that was used is associative method quantitative approach which purpose seeking influence between competence (variable X)  toward employee performance (Y). Primary data in this study were obtained through questionnaires as much as the number of samples is 72 Employees of Library institution, Archives and the documentation of Denpasar. Samples in this study using sampling techniques saturated. The results of the analysis of this study indicate that the variable competence affect positive and significant with the employee performance with regression equation Y = 19.188 + 0.377 X. The result R2 of 31.1%, and the remaining 68.9% is affected by other factors. From test of significance test obtained t (5.622) is bigger than t table (1.666) and showing competencies affect significant positive on employee performance in Badan Perpustakaan, Arsip dan Dokumentasi Kota Denpasar   Keywords: Competence, Employees Performance, Library, Archives and The Documentation of Denpasar